(untitled) (The Agriculturists, 2015)
This study was conducted to compare the productivity and profitability of trained and non-trained small-scale broiler farmers in the Joypurhat district of Bangladesh. A total number of sixty farmers were trained on the modern techniques for profitable and sustainable broiler farming. The study showed that the mortality of broiler was 2.90±0.89 percent and 11.30±2.29 percent for trained and non-trained farmers, respectively (P<0.001). Feed conversion ratio (FCR) was 1.65±0.08 and 1.75±0.10 for trained and non-trained farmers, respectively (P<0.01). The net profit was 18.60±2.77 and 8.74±2.05 taka per broiler for trained and non-trained farmers, respectively (P<0.001). It can be concluded from the present study that the family training would be a very essential tool for gaining more productivity and profitability of small scale broiler farming in Bangladesh. The Agriculturists 2014; 12(2) 137-141